Comparison of orthophoto using digital video plotter and matlab photogrammetric toolbox [electronic resource] - 380536 Wan Mohd. Faiz Wan Abd. Rahman (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik) - Universiti Teknologi Malaysia, 2008